Prioritizing Patient Perspectives When Designing Intervention Studies for Homeless Older Adults. (September 2021) - Canham, Sarah L.; Bosma, Harvey; Palepu, Anita; Small, Scott; Danielsen, Chris
Purpose: Medical respite provides postacute care to people experiencing homelessness upon hospital discharge if they are too sick to recover on the streets or in a traditional shelter. The current study examined the feasibility of conducting a study to test the effectiveness of a medical respite intervention for older people experiencing homelessness. Methods: Fifteen patient and 11 provider participants were interviewed between July and November 2018. Results: Participants' considerations for how to design a program of research included (1) desired qualities of researchers; (2) preferences for study design; (3) mechanisms for participant recruitment and retention; (4) what, where, and how to collect data; and (5) barriers and motivations to participation. Conclusions: Findings from this study build on an emerging research base on how to appropriately engage vulnerable patient groups, including older people experiencing homelessness, in trauma-informed research by including peer researchers on research teams to serve as advisors throughout the research process.